Research methods of emotional and volitional potential of highly qualified rowing athletes - Cheban, Y. (Science and Education, 2020)
The article presents the results of theoretical and empirical study of the issue of diagnosing the level of development of emotional and volitional potential of highly qualified rowing athletes in kayaking and canoeing. The relevance of the research topic is determined by the importance of emotional and volitional training of athletes to achieve maximum results in sports competitions. The psychological diagnosis of emotional and volitional potential is a necessary component of such training. The aim of the article is to explore the possibilities of psychological diagnosis of the development level of emotional and volitional potential of highly qualified rowing athletes. It is proposed to use four types of methods to study the emotional and volitional potential. The first one includes methods for determining the values of the available emotional and volitional potential on the basis of self-assessment and expert assessment and those which are based on certain specific test to determine the data of its reserve. The second one is focused on the diagnosis of various emotional and volitional personality traits such as emotionality, emotional maturity, anxiety, emotional stability, confidence, perseverance, self-control,etc. The third one includes methods of assessing such personal characteristics as achievement motivation; the level of development of cognitive processes, characterological features, as well as certain individual and dynamic data. The fourth one includes means of assessing the skills and abilities of self-stabilization in the prestarting situation and in the process of solving a competitive issue. The results of approbation the first type of methods showed that the data obtained through expert assessment of emotional and volitional potential of athletes, self-assessment of athletes` own potential and testing the emotional and volitional capabilities during physical exercises correspond to the objective achievements of rowers in sporting competitions and their sport qualifications. However, most of all it concerns the expert assessment.